Design as the basis for integrated STEM education: A philosophical framework - Hallström, Jonas; Ankiewicz, Piet (Frontiers in Education, 2023)
STEM—science, technology, engineering, and mathematics—has become important as an educational construct and phenomenon in recent years. However, it is only just recently that STEM education has begun to be examined from a philosophical point of view. There is therefore a need for further investigation of its philosophical basis, particularly in relation to integrated STEM education (iSTEM). Recent conceptual and empirical studies emphasize the crucial role of design in achieving successful STEM integration, and design thinking has also lately gained traction in such integration. The aim of this study is to investigate an integrated philosophy of STEM education, based on the methodological backbone of design. The research methodology consisted of a critical review of the literature regarding the philosophy of STEM (education), science, technology, engineering, mathematics, and STEM education research, related to the current issues of integrating the various STEM subjects. We thus base the philosophical framework on philosophy and studies from/on the STEM subjects in education. It is concluded that from a methodological point of view, design holds promising affordances for unifying the STEM subjects through “pure STEM problems”. Design as part of, for instance, particular engineering design projects may consequently require the “design” of applicable scientific experiments as well as mathematics expressions and formulae specifically when engaging in technological modeling.